La literatura española en Bulgaria hasta los años 80 del s. XX. Retrospectiva general - Dimitrova Láleva, Tania (Eslavística Complutense, 2003)
The articie study the introduction ofthe Spanish Literature in Bulgaria since XIX until the earlier 805 in the XX. It takes special interest to the literature, social and cultural processes that determine the transíation of certain texts or Spanish authors. It investigate the indirect transíation, in general terms throw French or Russian, this was typical at flrst, and it establish Ihe bridge-language. It discover the tendencies of the national Bulgarian literature that had been definitive in the acceptation of the Spanish literature in the difference ages.
Keywords: Spanish literature; Bulgarian literature; Literary traslation